Differential inhibition of gelatinase activity in human colon adenocarcinoma cells by Aloe vera and Aloe arborescens extracts - Ana Lima; Paula Batista-Santos; Eduarda Veríssimo; Patrícia Rebelo; Ricardo Boavida Ferreira (BMC, 2020)
Abstract Background Aloe's reported bioactivities (anticancer, anti-inflammatory and wound healing) suggest they might inhibit a subgroup of matrix metalloproteinases (MMPs) called gelatinases (MMP-2 and MMP-9). The goal of the present study was to compare the MMP inhibitory potential of two Aloe species, A. vera and A. arborescens. Methods Different types of extraction were tested and specific bioactive compounds were quantified. Cancer cell invasion inhibitory activities were measured in vitro using the wound healing assay in human colon cancer cells (HT29). Effects on gelatinase activities were further assessed by dye-quenched gelatin and gelatin zymography. Results Different types of extraction yielded significantly different levels of bioactivities and of bioactive compounds, which might be due to a greater amount of extractable bioactive compounds such as anthraquinones. Both A. arborescens and A. vera have potential as inhibitory agents in cancer cell proliferation via MMP-9 and MMP-2 enzymatic activity inhibition, being able to reduce colon cancer cell proliferation and migration but A. arborescens showed to be a more effective inhibitor of cancer cell migration than A. vera. Conclusion This work opens novel perspectives on the mode of action of Aloe species in cancer cell migration and may provide clues as to why there are so many conflicting results on Aloe's activities.